Moderating Role of Work Experience on Career Progression and Work Attitude - Ogunyemi, Ajibola O. (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
The present study was conducted to examine the moderating role of work experience in the relationship between career progression and work attitudes (job satisfaction and organizational commitment) among bank workers in Ogun State, Nigeria. The design adopted for this study was expost-facto survey design. A sample of 150 employees was chosen through stratified random sampling technique. The population was divided into three strata, which are the senatorial districts in Ogun State, namely, Ogun East, Ogun Central, and Ogun West.  Simple and multiple regression analyses were employed for data analysis. Results showed, among other things, that there was a significant contribution of career progression to job satisfaction (t = 9.228, p < .05) and organizational commitment (t = 7.008, p < .05) and that work experience does not significantly moderate the influence of career progression on work attitudes. The outcome of this study reveals that work experience had no significant moderating role in the influence of career progression on job satisfaction and organizational commitment which may be an indicator of the influence of career progression being so strong as to overshadow and render insignificant the influence of length of time spent in the organization. It was recommended, among other things, that organizations should formulate policies and create enabling environment that can foster career progression prospects among employees. Keywords: Work-experience, career-progression, work-attitudes, job-satisfaction, organizational -commitment.